The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1094/pdis-93-11-1195
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Cluster Compactness and Bunch Rot in Vignoles Grapes

Abstract: The impact of cluster compactness and debris retention on harvest bunch rot of Vitis interspecific hybrid ‘Vignoles’ was investigated between 2001 and 2005 near Lake Erie, in Pennsylvania. Cluster compactness was characterized subjectively based on the OIV code 204 standard and objectively by determining the number of berries per centimeter of rachis. In 2001, 2002, and 2004, the median number of berries per centimeter for loose clusters was 6.3, 7.0, and 6.4 compared with 10.2, 12.7, and 12.4 for the compact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
96
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 13 publications
3
96
1
1
Order By: Relevance
“…A combination of frequent rain and sustained humidity, particularly in spring and summer, provided conditions for leaves and berries remain wet, enabling infections by P. viticola and B. cinerea. Previous studies have shown that for P. viticola, optimal growth is at temperatures of 20-25°C (Madden et al, 2000;Kennelly et al, 2005) and B. cinerea growth is optimal at 15-23°C (Wilcox, 2005;Hed et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…A combination of frequent rain and sustained humidity, particularly in spring and summer, provided conditions for leaves and berries remain wet, enabling infections by P. viticola and B. cinerea. Previous studies have shown that for P. viticola, optimal growth is at temperatures of 20-25°C (Madden et al, 2000;Kennelly et al, 2005) and B. cinerea growth is optimal at 15-23°C (Wilcox, 2005;Hed et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Any time after bloom, under high humidity, the floral debris will produce spores that can infect the rachis and other cluster parts. The initial symptoms of the disease occur in the internal tissues of the berry; the berry turns dark -which is easy to observe in a white variety like 'Sauvignon Blanc' -, the pulp softens, and the skin easily splits or slips off the pulp when touched (Hed et al, 2009). …”
Section: Podridão Cinzenta Em Videira 'Sauvignon Blanc' Sob Sistemas mentioning
confidence: 99%
“…Grape cultivars, such as Sauvignon Blanc, with dense canopies, thin skins, and/or compact clusters are more susceptible to botrytis bunch rot (Hed et al, 2009), since their ripening stage and harvest season coincide with the period of heavy rain (average of 195 mm per month) in Southern Brazil. According to Bem et al (2015), the vertical shoot-positioned training system, compared with the Y-trellis one, reduced botrytis bunch rot intensity in 'Cabernet Sauvignon' under the edafoclimatic conditions of the highlands of the state of Santa Catarina.…”
Section: Podridão Cinzenta Em Videira 'Sauvignon Blanc' Sob Sistemas mentioning
confidence: 99%
See 2 more Smart Citations